Portuguese Principals' Professional Development Needs and Preferred Learning Methods - Rosário Serrão Cunha; Mireia Tintoré; Ilídia Cabral; José Matias Alves (MDPI AG, 2020)
Due to the crucial role principals have on school outcomes, investing in their training is a cost-effective approach for schools' improvement. Research shows that principals attribute pertinence to their ongoing professional development. However, little research has been conducted on principals' training needs from their viewpoint, particularly in Portugal. Through individual interviews (n = 19) and a questionnaire (n = 117) to principals, we collected data that enable us to understand principals' perceptions on their training needs, focusing on learning areas, skills to be developed and learning methods. Results show considerable variability, reinforcing the relevance of tailored and contextualised approaches to professional development. Globally, principals request management skills and training opportunities that enable them to develop leadership skills (e.g., personal, interpersonal/socioemotional). Moreover, principals need training on instructional and distributed leadership practices. Collaborative and reflective methods are the ones principals prefer. Practical implications for the design of systematic professional development practices, in a lifelong perspective, are also discussed.